Design of an electropneumatic shedding mechanism for a sampling loom. Issue 6 (14th May 2021) - Ala, Deniz Mutlu; Çelik, Nihat
Abstract: An electropneumatic shedding mechanism has been designed and developed for making a prototype sampling loom with having computer-controlled shedding in our project supported by Turkish Government. In the study, in order to choose the best suited healds and heald frame movement distance for shedding system, different shedding geometries were studied and compared in relation to the cloth fell distances and warp elongation in fully open-shed positions. Mechanical and electrical designs were based on the most effective shed geometry. This article includes the developed shedding mechanism, comparison of the shed geometries drawn by using Solidworks® as well as the strength analysis of pneumatic pistons.